Difference of Calcium Levels in Infants with Low Birth Weight - Nugraha, Sandi; Salimo, Harsono; Hidayah, Dwi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Hypocalcemia is a condition that can cause serious disorders, especially in newborns. The occurrence of hypocalcemia is an event that often occurs in babies born that can be caused due to late parathyroid hormone function in calcium metabolism in the baby's body. Hypocalcemia is often associated with hypotension and disorders of the heart rhythm, symptoms that are often seen are apnea, tachycardia, lethargy, vomiting, and gastrointestinal disorders. This study aimed to analyze differences in calcium level between low birth weight infants.Subjects and Method: A cross sectional study was conducted at Dr Moewardi Hospital, Surakarta, Central Java, from December 2016 to April 2017. A sample of 158 LBW children was selected using consecutive sampling. The dependent variable is a decrease in calcium levels. The independent variable is low birth weight babies. Data collected by medical records. Data were analyzed using multiple logistic regression.Results: Calcium level ≥1.13 mmol/L (OR= 0.30; 95% CI= 0.15 to 0.57; p <0.001), no seizures (OR= 0.20; 95% CI= 0.06 to 0.64; p = 0.004), and QoTC (OR= 0.20; 95% CI= 0.07 to 0.572; p= 0.003) decreased the risk of low birth weight.Conclusion: Calcium level ≥1.13, no seizures, and QoTC decrease the risk of low birth weight.Keywords: low birth weight, hypocalcemiaCorrespondence: Sandi Nugraha. Department of Pediatrics, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta. Phone/Fax.0271-633348. Email:sssandinugraha@gmail.comIndonesian Journal of Medicine (2020), 05(02): 131-136https://doi.org/10.26911/theijmed.2020.05.02.06